Psychological Indicators Ensuring Efficiency of the Chess Player's Competitive Activity - Geghamyan, Vardan; Tarjumanyan, Silvi (Physical Education Theory and Methodology, 2023)
The work is based on the discussion of psychological problems in modern chess, which are significantly related to the rapid growth of chess competitiveness in recent years, the frequency of participation in competitions, the intensity of competition and other similar manifestations. The study purpose. We tended to identify the most important psychological indicators that ensure the effectiveness of the chess player's competitive activity, to describe their correlational relations and the peculiarities of their manifestation. Materials and methods. The research process was carried out with interconnected laboratory-instrumental and non-instrumental methods, which are of great practical importance in psychology: questionnaires, tests, observations, mathematical statistical methods, as well as self-made "psychodiagnostic multifactorial" equipment. The research was organized among 30 grandmasters in the National men's chess team of the Republic of Armenia through different years, winners of the World Olympiad, World team tournaments, and the World Cup. It targeted the study of the four main areas of a chess player's psyche: competitive mental reliability, individual psychological characteristics, emotional states and emotional abilities. Results. As a result of the analysis of correlations, the following 8 patterns were singled out from 52 examined psychological indicators: stability to internal uncertainty stressors, competitive emotional endurance, personal anxiety, energetic sphere of competitive motivation, psycho-regulation, mobilization preparedness, attention features and complex motor reaction speed. We consider the selected indicators as the leading psychological factors that ensure the competitive process of the chess player. Conclusions. Effective manifestations of selected psychological indicators can enable a chess player to perform in a more stable and effective way during decisive competitions. The selected indicators can also describe the level of sports training of a highly qualified chess player and serve as model characteristics of psychological service.